Utilizing a Data-to-Action Approach to Cultivate Policy Research and Advocacy Skills in Community-Engaged Health Promotion Courses. (September 2022) - Batada, Ameena; Thomas, Audrey E.; Holtz, Danielle
Community-engaged (or service) learning is a common approach in health promotion and undergraduate education and can provide students with an opportunity to learn about the social determinants of health and policy change and advocacy. Students can support organizations with policy advocacy to promote more equitable resource allocation in communities close to campus and take these skills into their future professions. This article presents an overview of and the lessons learned from a "data-to-action" approach, as well as a summary of students' perceptions on being part of a class taking this approach. In partnership with community organizations advocating for policy change, a data-to-action approach engages and guides students in primary and/or secondary data collection, analysis, and reporting. Through the projects described in this article, students observed how policy change can affect the social determinants of health, and they contributed to advocacy efforts for policy change, such as extending bus routes, reducing the marketing and sales of tobacco, and prioritizing resources for people who are houseless. Overall, students reported that they gained familiarity with local communities and with research and other professional skills. A data-to-action approach has the potential to benefit both students and community organizations' local advocacy efforts.